Surah An-Nasr Kajian Stilistika Al-Qur’an - Nasution, Aminullah Nasution (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Abstrak Surah an-Nasr is the last surah revealed which contains Allah's help for those who believe. Surah an-Nasr was chosen because of its beautiful and distinctive style of language to be discussed from a stylistic perspective. This study focuses on surah al-Nasr with the aim of analyzing the text based on five stylistic aspects, namely phonology, morphology, syntax, semantics and imagery. The material object in this study is surah an-Nasr and the formal object is the style of language contained in surah an-Nasr, With a linguistic approach, aesthetic elements in a text can be expressed. One of the linguistic approaches is stylistics, with the theory expected to be able to explain the phenomenon of deviation and also language preferences. This research is a literature research using qualitative methods. The results of this study are 1) Surah al-Nasr has a perfect style of language, both in terms of sound aesthetics, words and sentences, 2) the selection of more fricative consonants than flossive consonants, in accordance with the meaning contained in surah an-Nasr, 3) In Surah an-Nasr, it is found that there are deviations or preferences from aspects of morphology, syntax, semantics, both from the form of words or sentences that make Surah an-Nasr has its own meaning, 4) Surah an-Nasr contains an element of beauty, namely Isti’a>rah makniyah. Keywords: Stylistics, al-Nasr, Language Style.